2022
DOI: 10.25259/sni_992_2022
|View full text |Cite
|
Sign up to set email alerts
|

Review of anterior cervical diskectomy/fusion (ACDF) using different polyetheretherketone (PEEK) cages

Abstract: Background: Multiple anterior cervical diskectomy/fusion (ACDF) techniques now use a variety of Polyehteretherketone (PEEK) cages; stand-alone (SA) and zero-profile (ZP) with/without screws, cages filled with demineralized bone matrix/autograft, and cages coated with hydroxyapatite or titanium. We compared the safety/ efficacy between different PEEK ACDF cage constructs in 17 studies, and in some cases, additionally contrasted results with “routine” ACDF (i.e. series/historical data performed with combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…However, titanium is less elastic than other materials 12 . In contrast, PEEK cages are made to be elastic to redistribute the axial skeletal load and are bio-inert, which reduces the risk of infection but also may lower osteogenic potential 13 . Krause et al 9 and Teton et al 14 showed a 5 and 6-fold increase in risk of pseudarthrosis with PEEK cages compared with allograft and D’Antonio et al 15 showed that PEEK cage implantation was independently associated with postoperative pseudarthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, titanium is less elastic than other materials 12 . In contrast, PEEK cages are made to be elastic to redistribute the axial skeletal load and are bio-inert, which reduces the risk of infection but also may lower osteogenic potential 13 . Krause et al 9 and Teton et al 14 showed a 5 and 6-fold increase in risk of pseudarthrosis with PEEK cages compared with allograft and D’Antonio et al 15 showed that PEEK cage implantation was independently associated with postoperative pseudarthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the use of polymers to address the unmet needs of each clinical field in terms of mechanical properties comparable to those of metals, ease of surface modification for drug delivery, and biodegradation is being conducted continuously. For example, polyetheretherketone for orthopedic cervical cages, polylactic acid (PLA) for cardiovascular bioabsorbable stents, and polyvinyl alcohol for oral mucosal adhesive drug delivery systems have been reported [28][29][30]. Among various polymers, in particular, PLA is the most commonly used biodegradable polymer in clinical applications today.…”
Section: Introductionmentioning
confidence: 99%
“…However, Ti cages have relatively higher elastic modulus (110 GPa) and a stress shielding effect; hence, there is an increased risk of these cages subsiding post surgery. Further, the radiopacity of these cages makes it difficult for surgeons to determine postoperative fusion [7,8]. With the advancement in material science, polyetheretherketone (PEEK) cages are extensively used for spinal fusion procedures [9].…”
Section: Introductionmentioning
confidence: 99%